POLICYMAKING IN FAVOUR OF WOMEN: LEARNING FROM THE GENDERED IMPACT OF COVID-19, WITH A FOCUS ON SOUTH AFRICA - Fluks, Lorenza; Groenewald, Candice; Qoza, Phiwokazi; Isaacs, Nazeema; Essop, Roshin; Couch, Marilyn; Essack, Zaynab; van Rooyen, Heidi (Social Work/Maatskaplike Werk, 2024)
Realisation of women’s full participation in all spheres of society remains inconsistent and progress towards gender equality is slow. The COVID-19 pandemic laid bare existing and deeply entrenched gender inequalities. In this article, we draw on multiple HSRC-led studies conducted between 2020 and 2022 that explored the impact of the COVID-19 pandemic and lockdown on the psychosocial and economic wellbeing of women and their families. We show that many women at the community and household level took up the majority share of unpaid household and childcare duties, and faced persistent socio-economic threats, gender-based violence and increased mental health concerns compared to their male counterparts – all of which impeded their ability to lead productive and fulfilling lives. Insights are offered for intersectional gender-responsive policy responses that favour women as central role players in families and the economy.